Biochar impact on the estimation of the colorimetric‐based enzymatic assays of soil. (23rd July 2019) - Cardelli, Roberto; Becagli, Michelangelo; Marchini, Fausto; Saviozzi, Alessandro
Abstract: This study was carried out in order to assess the influence of biochar applications on the estimation of colorimetric‐based enzymatic assays and to verify the effectiveness of the most common methods. Since most methods used to determine enzymatic activities in the soil are based on colorimetry, biochar may absorb substrates and/or coloured products thereby distorting the analytical result. Biochar was added to two soils, with different textures and cation exchangeable capacities, at a rate of 2% (w/w), and seven enzyme activities were determined following standard methods. The biochar amendment lowered the spectrophotometer reading of the activity of FDAase and dehydrogenase in the sandy soil. In the three enzymatic activities based on p‐nitrophenol production (β‐glucosidase, phosphatase and arylsulphatase), the addition of biochar did not change the enzyme assays. The biochar led to an overestimation in terms of the protease and urease activities in the sandy soil. In the clay loamy soil, biochar did not change the response of any of the enzyme activities tested. A biochar dose of up to 2% only guarantees the effectiveness of the most common spectrophotometric methods for not excessively sandy soils.